Technologija kondicionnoj i techniceskoj podgotovki begunov - Skripko, A. D.; Popov, G. I. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The article is about the usage of training devices for the development of physical abilities. The purpose of the research was to examine the conditions for training of elite athletes. The article is the generalization of the long-term pedagogical experience, the authors' researches in the field sport training, trainer facilities and biomechanics. The paper is addressed to researches, trainers and athletes.